2021
DOI: 10.1262/jrd.2021-026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oocyte-derived growth factors on the growth of porcine oocytes and oocyte–cumulus cell complexes <i>in vitro</i>

Abstract: During oocyte growth and follicle development, oocytes closely communicate with cumulus cells. We examined the effects of oocyte-derived growth factors, growth differentiation factor 9 (GDF9) and bone morphogenetic protein 15 (BMP15), on the growth and acquisition of meiotic competence of porcine oocytes collected from early antral follicles (1.2-1.5 mm). First, we confirmed that GDF9 and BMP15 mRNAs were expressed almost exclusively in the oocytes. Oocyte-cumulus cell complexes (OCCs) collected from early ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…In contrast, BMP15 did not significantly increase the OCC diameter or the formation of antrum-like structures. These results were mostly similar to the results obtained in our previous report [ 24 ], which suggested that GDF9 promoted the proliferation of cumulus cells to increase complex diameter, while BMP15 had little or no effect on OCC development. GDF9 promotes the proliferation of cultured granulosa cells in various species [ 7 , 21 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In contrast, BMP15 did not significantly increase the OCC diameter or the formation of antrum-like structures. These results were mostly similar to the results obtained in our previous report [ 24 ], which suggested that GDF9 promoted the proliferation of cumulus cells to increase complex diameter, while BMP15 had little or no effect on OCC development. GDF9 promotes the proliferation of cultured granulosa cells in various species [ 7 , 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…To collect and handle ovarian follicles and OCCs, 25 mM HEPES-buffered medium 199 (HEPES-199; Nissui Pharmaceutical, Tokyo, Japan) containing 0.1% (w/v) polyvinyl alcohol (PVA), 0.85 mg/ml sodium bicarbonate, and 0.08 mg/ml kanamycin sulfate was used. The basic growth medium was Minimum Essential Medium α (GIBCO Invitrogen, Paisley, UK) supplemented with 2.2 mg/ml sodium bicarbonate, 0.08 mg/ml kanamycin sulfate, 2% (w/v) polyvinylpyrrolidone (molecular weight 360,000), 55 µg/ml L-cysteine, 0.05 µM dexamethasone, 4.0 mM hypoxanthine, 50 µg/ml ascorbic acid 2-glucoside (Hayashibara, Okayama, Japan), 10 µM 17β-estradiol, 0.01 IU/ml Gonalef 75 (recombinant human follicle-stimulating hormone; Merck Biopharma Japan, Tokyo, Japan), and 5% (v/v) fetal bovine serum (ICN Biomedicals, Costa Mesa, CA, USA) as reported previously [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations